Multi-Scale, Multi-Proxy Investigation of Late Holocene Tropical Cyclone Activity in the Western North Atlantic Basin - Oliva, François (Université d'Ottawa / University of Ottawa, 2017)
Paleotempestology, the study of past tropical cyclones (TCs) using geological proxy techniques, is a growing discipline that utilizes data from a broad range of sources. Most paleotempestological studies have been conducted using “established proxies”, such as grain-size analysis, loss-on-ignition, and micropaleontological indicators. More recently researchers have been applying more advanced geochemical analyses, such as X-ray fluorescence (XRF) core scanning and stable isotopic geochemistry to generate new paleotempestological records. This is presented as a four article-type thesis that investigates how changing climate conditions have impacted the frequency and paths of tropical cyclones in the western North Atlantic basin on different spatial and temporal scales. The first article (Chapter 2; Oliva et al., 2017, Prog Phys Geog) provides an in-depth and up-to-date literature review of the current state of paleotempestological studies in the western North Atlantic basin. The assumptions, strengths and limitations of paleotempestological studies are discussed. Moreover, this article discusses innovative venues for paleotempestological research that will lead to a better understanding of TC dynamics under future climate change scenarios. The second article (Chapter 3; Oliva et al., submitted, The Holocene) presents the development of the first database summarizing the most up-to-date paleotempestological proxy data available for TC reconstructions for the western North Atlantic basin. Subsets of this new database are then used to reconstruct TC variability in the western North Atlantic basin. Using our new developed subsets, we investigate a key hypothesis, the Bermuda High Hypothesis that has been proposed to have influenced TC paths over centennial to millennial timescales. Results show an oscillation in the distribution of TC landfalls along the North American coast, suggesting a centennial oscillation in the mean summer position of the high pressure system. We suggest that a more serious, millennial scale shift in the Bermuda High to a northeastern (NE position) may have occurred at ~3000 and ~1000 cal yr BP. The third article (Chapter 4; Oliva et al., under review, Marine Geology) presents a local multi-proxy reconstruction of TC activity during the past 800 years from Robinson Lake, Chezzetcook Inlet in Nova Scotia, Canada. Here, we are testing the more recent use of the XRF scanning approach to paleotempestology at a local scale. Two sediment cores were extracted from Robinson Lake that were dated by 210Pb and 14C, analyzed for organic matter content, benthic foraminifera and thecamoebians, sediment grain size, and a range of elements and elemental ratios determined by XRF core scanning. Results show two periods of low TC activity based on multiple proxies including XRF technology: one from ~1150 to 1475 CE (800 – 475 cal yr BP) and the other from 1670 CE (280 cal yr BP) to the present, with the intervening period from ~1475 to 1670 CE (475 – 280 cal yr BP) as a time of more frequent and possibly higher magnitude TC activity. The fourth article (Chapter 5. Oliva et al., in preparation, Canadian Journal of Earth Sciences) explores the potential use of stable oxygen isotopes in tree ring α-cellulose to reconstruct past local TC activity surrounding areas of known TC strikes. Cores of 12 Picea mariana trees were extracted adjacent to Robinson Lake, Chezzetcook Inlet, Nova Scotia in order to test more contemporary and historically documented records of TC activity in this region as per Chapter 4. TCs precipitate 18O-depleted rain, leaving a unique signature in the source water that trees use to form cellulose. Using an autoregressive integrated moving average (ARIMA AR-1) model to detrend the data, local and regional time series were reconstructed. Local reconstructions led to most (> 95%) hurricanes and all major hurricane (± 1 year) being recorded in the isotope record, whereas the regional reconstruction shows no major hurricane, only a few hurricanes (< 40%) and one signal with a higher error (> 1 year). This thesis contributes to advancing our knowledge in paleotempestology of the western North Atlantic basin by: 1) bringing an up-to-date current status on paleotempestology, 2) the development and ongoing use of a new paleotempestology database for the western North Atlantic basin publicly available, 3) a local scale study using new XRF core elemental technology and 4) the exploratory use of tree-ring α-cellulose oxygen isotopic analysis based on contemporary and historical documents at local sites.